A narrative inquiry of Sudanese Muslim women’s perceptions of their integration into the Finnish society in Jyvaskyla City - Assaf, Ahkam (2019)
This study examines five Muslim, Sudanese women's experiences of integration in Jyvaskyla city, Finland. It is an attempt to understand the study participants’ lived experiences of integration from a micro perspective. The focus of this study is to shed light on the obstacles and aids of integration, and unfold the meanings attached by the study participants to their experiences of integration in Finland. In order to meet the study objectives and answer the research questions, a qualitative design is utilized, and narrative inquiry is used to collect data. Data analysis reveals that the major dilemma for all the study participants is child-rearing in a culture of values and mores conflicting with the Islamic, Sudanese values. Another dilemma is lack of Finnish language skills, which did obscure the study participants' ability to express their needs and voice their concerns in the early stages of their life in Finland. Moreover, high living standards and lack of good work opportunities are considered as a burden by the study participants. On the other hand, the findings highlight aids of integration. For example, the participants are found out to be resilient as they have formed strategies to help them integrate. For example, the Muslim, Sudanese women have used strategies to tackle racism and intolerance incidents, which are, surprisingly, few. Solidarity was shown by Finnish people in the place where racism and intolerance took place. Moreover, the Muslim, Sudanese women did not isolate themselves from the Finnish society but made networks with Finnish people in spite of the Finns' social shyness. Finally, the public officials' conduct is deemed to facilitate the participants’ integration.